The Bacteriophage Lambda gpNu3 Scaffolding Protein Is an Intrinsically Disordered and Biologically Functional Procapsid Assembly Catalyst - Medina, Eva Margarita (2011)
Procapsid assembly is a process whereby hundreds of copies of a major capsid protein assemble into an icosahedral protein shell into which the viral genome is packaged. The essential features of procapsid assembly are conserved in both eukaryotic and prokaryotic complex double-stranded DNA viruses. Typically, a portal protein nucleates the co-polymerization of an internal scaffolding protein and the major capsid protein into an icosahedral capsid shell. The scaffolding proteins are essential to procapsid assembly. Here, we describe the solution-based biophysical and functional characterization of the bacteriophage lambda (λ) scaffolding protein gpNu3. The purified protein possesses significant α-helical structure and appears to be partially disordered. Thermally induced denaturation studies indicate that secondary structures are lost in a cooperative, apparent two-state transition (T(m) =40.6±0.3 °C) and that unfolding is, at least in part, reversible. Analysis of the purified protein by size-exclusion chromatography suggests that gpNu3 is highly asymmetric, which contributes to an abnormally large Stokes radius. The size-exclusion chromatography data further indicate that the protein self-associates in a concentration-dependent manner. This was confirmed by analytical ultracentrifugation studies, which reveal a monomer–dimer equilibrium (K(d,app) ~50 μM) and an asymmetric protein structure at biologically relevant concentrations. Purified gpNu3 promotes the polymerization of gpE, the λ major capsid protein, into virus-like particles that possess a native-like procapsid morphology. The relevance of this work with respect to procapsid assembly in the complex double-stranded DNA viruses is discussed.